1982
DOI: 10.1021/ja00383a014
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation of hydrocarbons. 11. Kinetics and mechanism of the reaction between methyl (E)-cinnamate and quaternary ammonium permanganates

Abstract: A study of the reaction of methyl (£)-cinnamate with quaternary ammonium permanganates in methylene chloride solutions has been completed. The rate of reaction is fastest for those ions which permit the interionic distance in the quaternary ammonium ion pair to be minimized. The Hammett p value for the reaction is 0.95 at 20 °C, and an inverse secondary deuterium isotope effect is observed at the ß-position but not at the «-position. The sign of the p value for this reaction is in direct contrast to the report… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
46
0

Year Published

1982
1982
2010
2010

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 70 publications
(49 citation statements)
references
References 1 publication
3
46
0
Order By: Relevance
“…Plots of In (A -A 3 against time were linear (lo), thus indicating that the reaction is first order in pennanganate. The pseudo-first-order rate constants, obtained from the slopes of these plots, were found to be directly proportional to the concentration of the reductant, thereby confirming that the reaction is also first order in reductant concentration (10).…”
Section: Kineticsmentioning
confidence: 64%
See 2 more Smart Citations
“…Plots of In (A -A 3 against time were linear (lo), thus indicating that the reaction is first order in pennanganate. The pseudo-first-order rate constants, obtained from the slopes of these plots, were found to be directly proportional to the concentration of the reductant, thereby confirming that the reaction is also first order in reductant concentration (10).…”
Section: Kineticsmentioning
confidence: 64%
“…Since some substituted alkenes (such as methyl cinnamates) that are capable of delocalizing negative charges exhibit positive p values, while other alkenes (such as vinyl ethers) that are able to stabilize positive charges exhibit negative p values, it is not surprising that for certain reactions, the sign of p actually changes when different substituents are present. The oxidation of substituted stilbenes, which has been studied by Henbest et al (28), is one example of this phenomenon; the rate of reaction is accelerated by both electron-donating and electron-withdrawing substituents (10). The oxidation of substituted P-methoxy and P-bromostyrenes also gives Hammett plots with a distinctive Can.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since there is an overwhelming abundance'bf evidence (3) that these reactions are initiated by the formation of a cyclic manganese(V) diester, 1, it has previously been suggested that the detected product of the reaction could actually be a dimer or a polymer of 1 (5). This possibility appears, however, to be inconsistent with an oxidation state of +4, and with the observation that products of similar properties are also obtained from the reduction of permanganate by alkynes, alcohols, and amines under these conditions (Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…Equation [5] implies that a linear relationship should exist between A(526) and A(418). However, Fig.…”
Section: Discussionmentioning
confidence: 99%